Heat transfer in the dynamic cycling of lithium–titanate batteries. (February 2016) - Wang, Qingsong; Sun, Qiujuan; Ping, Ping; Zhao, Xuejuan; Sun, Jinhua; Lin, Zijing
Highlights: The temperature variation of a 945 mA h lithium–titanate battery was investigated. The simulation and experimental results agree well at the current rate of 0.5 C. Two temperature peaks were observed during a discharge–charge cycle. The temperature rise rapidly both at the initial stage and the end of discharging. Radiation contributes about 42.11% to heat transfer in natural cooling condition. Abstract: Based on the coupled model of a three-dimensional thermal model and one-dimensional electrochemical model, the thermal behaviors of lithium–titanate battery under the discharge–charge cycling with various current are investigated. The temperature on the surface of battery increases with the increasing cycling rate. Two temperature peaks are observed during the constant-current discharge, constant-current and constant-voltage charge process based on the analysis of the heat generation. Additionally, the radiative heat transfer cannot be omitted when the battery is operated under natural convection at 0.5 C cycling rate, in this case, the radiative heat transfer is estimated to contribute 42% to the total heat transfer. The results can provide basic data for the thermal management of the battery pack during the discharging and charging processes.